Effects of exposure to predator models on fledging behaviour in blue tits. (November 2021) - Santema, Peter; Schlicht, Lotte; Beck, Kristina B.; Kempenaers, Bart
Abstract : Leaving the nest is a key transition in the life of altricial birds, whereby fledging decisions should depend on multiple factors, including the risk of predation. High postfledging predation risk may favour fledging at a more advanced stage of development, if more developed fledglings are better at escaping predation, or together with others. While comparative studies have highlighted the role of predation risk for between-species variation in the timing of fledging, drivers of within-species variation in fledging behaviour remain largely unknown. We presented owl models near blue tit, Cyanistes caeruleus, nests during the first half of the day throughout the fledging period to simulate an increased risk of postfledging predation. Using an automated monitoring system, we then recorded the precise fledging times of 595 nestlings from 105 nests (52 predator-treated, 53 control nests). Contrary to our predictions, the predator presentations did not affect the age at which nestlings fledged, the time of day of fledging or other aspects of fledging behaviour. The tendency to fledge together with siblings was affected, but the effect was in the opposite direction to that expected, with nestlings exposed to the predator treatment being more likely to fledge alone. Parents visited predator-treated nests less often, but this effect diminished over the course of the morning. We suggest several explanations for why the behavioural responses to the predation risk manipulation were generally limited. Highlights: In altricial birds, the duration of the nestling period varies substantially. Time of fledging may depend on relative risk of pre- and postfledging predation. We presented owl models near blue tit nests to simulate increased predation risk. The treatment did not affect the age or time of day at which nestlings fledged. The treatment did affect other aspects of fledging and parental behaviour.